Design and European firms' innovative performance: A less costly innovation activity for European SMEs? - Daria Ciriaci (European Commission, Joint Research Centre (JRC), 2011)
The objective of this study is to provide an analysis of the importance of design – defined as the procedures, choice of elements and technical preparation to implement a new product – and R&D investments as drivers of European firms' innovation performance. In doing so, it partly compensates for the lack of empirical evidence in the literature by using non-anonymised data from the third wave of the European CIS, and estimating a system of simultaneous equations to tackle the endogeneity inherent in these investment choices and the externalities associated with them. The choice to use this time period rather than more recent is data-driven as this wave contains better information on design expenditures. Unlike the majority of CIS-based studies, the main variables of interest are continuous ones. In addition, although pure aesthetic changes are not included in the CIS definition of innovative design expenditures, the impact of this important dimension of product innovativeness is properly accounted for. The robustness of results confirms the crucial role of design investment for innovation success in 23 European countries for both the manufacturing and service sectors and its role as a complement to technological R&D and as a driver for user-centred incremental (new-to-the-firm) and radical (new-to-the-market) innovations. In particular it found an increase of 1% expenditure increases innovation sales by between 0.34% and 0.49%, while the same increase in R&D investment increases innovation sales by between 0.64% and 0.86%. Interestingly, while investing in design shows no statistically different innovation output returns for small, medium-sized and large enterprises, this is not the case for R&D expenditures. The policy conclusions are clear: design is a less costly alternative to R&D for many SMEs and a policy of supporting design should be considered, as this might be a more cost-efficient support strategy.
Keywords: 330; Intangibles; design; R&D investment; CIS; CDM model